Measuring and comparing planning cultures: risk, trust and co-operative attitudes in experimental games. Issue 6 (2nd June 2020) - Li, Keyang; Dethier, Perrine; Eika, Anders; Samsura, D. Ary A.; van der Krabben, Erwin; Nordahl, Berit; Halleux, Jean-Marie
ABSTRACT: Cultural impacts in planning increasingly receive attention from both academics and practitioners around Europe. However, comparative planning cultures studies face the challenges of lacking systematic comparison and empirical evidence, especially at the micro level of planning actors' behaviour in interaction. This article aims to fill these gaps by (1) operationalizing the concept of planning culture; and (2) measuring and comparing it. We base our operationalization on the culturized planning model (Knieling, J., & Othengrafen, F. (Eds.). (2009). Planning cultures in Europe: Decoding cultural phenomena in urban and regional planning . Farnham: Ashgate). We complement its explanatory power by building a link between planning culture and planning outcome through attitudes of planning actors. This article focuses on three attitudes: risk, trust and co-operation. To measure and compare these attitudes, we adopt three experimental economic games and conduct an experiment with public and private planning practitioners in three European countries: Belgium, the Netherlands and Norway. Both cross-country and public-private differences in these attitudes are tested in the experiment. Our experimental findings suggest that Dutch planning actors value risk aversion and trust; Norwegian planning actors value cooperation; while (French-speaking) Belgian planning actors do not value these variables that much.